Utilising the community cultural wealth framework to explore Sierra Leonean parents' experiences of outdoor adventure education in the United Kingdom. Issue 2 (3rd April 2022) - Cook, Rachel
ABSTRACT: Research exploring race and ethnicity and outdoor adventure education (OAE) has tended to focus on students' experiences. This paper discusses findings from a small-scale empirical study of Sierra Leonean parents involved in organising their child's participation in a camping-based, OAE residential visit. The visit was organised by one primary school in London (UK). The community cultural wealth framework by Yosso is utilised to explore the parents' contributions to the visit. The findings reveal the ways in which parents strove to meet the expectations placed on them and overcame challenges of facilitating the visit by drawing on aspirational, familial, navigational, resistant and social capital. Additionally, the role of spiritual capital is discussed. I conclude with recommendations for the ways in which the schools and providers of OAE could take account of ethnic minority parents' perspectives and experiences.